Knowledge, attitude and preparedness of healthcare students toward basic life support at King Khalid University, Abha, Kingdom of Saudi Arabia - Sirajudeen Shaik Alavudeen; Viqar Basharat; Ahmed Khaled Bahamdan; Vigneshwaran Easwaran; Ghadah Khaled Bahamdan; Md Sayeed Akhtar; Sultan Alshahrani; Ali Alqahtani; Krishnaraju Venkatesan (Clinical and Experimental Hypertension, 2022)
Background Worldwide, millions of people die of sudden cardiac arrest every year. A well-timed cardiopulmonary resuscitation (CPR) increases the possibility of survival by two- to fourfolds. This study aimed to assess the knowledge, attitude, and preparedness of health care students toward basic life support (BLS) at King Khalid University. Methods A cross-sectional study was conducted among the health care students of King Khalid University from August to October 2020. Data were collected using a pretested, semi-structured questionnaire and the data were analyzed using Statistical Package for the Social Sciences. Resulrs The total number of participants was 346. Overall, the participant’s knowledge regarding the BLS was inadequate. Majority of the participants were not aware of the acronyms used in BLS. The level of education has a significant impact on the knowledge, whereas gender has no significant impact on the knowledge. The answers to the attitude and the preparedness items were also not satisfying. Lack of knowledge is one of the common reasons for not performing BLS. Periodical training program and refresher courses were the most recommended methods to increase the knowledge toward the BLS. Conclusion It is evident from the current study that there is a lack of knowledge and preparedness toward BLS among most health care students. It is recommended to incorporate more BLS training and refresher courses in the health care college curricula.